Model of Multi Product Classification with Regular Demand on Inventory System in a Raw Material Supply Company - Tri Febrion; Joniarto Parung (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
The right strategy in inventory is the main point in maintaining adequate and guaranteed supply continuity. Inventory strategies are becoming important but complex when the number of items that must be prepared is increasing. In this regard, it is necessary to analyze the product groupings in several classifications. Prioritized products receive special attention.The same problem is faced by PT PEKA, an import raw material distribution company that has nearly 2000 product items. Based on data demand is known, that the company's demand does not have a fixed pattern. Many products have regular and irregular demand, even the number of regular demand is very volatile. Companies often experience excess stock or vice versa due to lack of stock demand according to predictions, long lead times and product self-life that varies. Related to this, alternative product groupings or classifications are needed in accordance with company conditions. The company currently has frozen and unfrozen products, has items made from natural and non-natural raw materials and has a short and relatively long lead time.PT. PEKA groups products in various stages, which lead to a combination of ABC and XYZ classifications. Demand of priority items generated from the grouping is then forecast according to the model that gives the smallest MSE / MAD. Furthermore, a case study was carried out to calculate the Total Relevance Cost (TRC) from the calculation results to be compared with the real TRC. TRC according to the classification results was Rp. 1,293,370,148, - lower than the actual condition TRC, which amounted to Rp. 1,805,887,874, -